Microstructure and Homogenization Process of Large Ingot of As-cast Condition C650R Nickel-based Alloy - Kou Jinfeng, Bai Yaguan, Nie Yihong, Zhang Xin, Zhang Bingbing, Li Jinshan, He Yixuan (Teshugang)
Using optical microscope， scanning electron microscope and energy dispersive spectrometer， the casting microstructure of 12 tons of ingots of as-cast condition C650R nickel-based alloy used in the 650 ℃ultra-supercritical steam turbine rotor， smelted by the three-process method （VIM+PESR+VAR）， and the microstructure after different homogenization treatments were studied. The high-temperature thermoplasticity before and after homogenization treatment was also compared. The results show that in the self-consumption ingots of ϕ960 mm ingot size produced using the three-process smelting method， there is a significant segregation. The main segregation elements are Mo， Nb， and Ti， which are segregated between dendrites. Within the crystal， the main precipitated phase is a MC-type primary carbide rich in Mo， Nb， Ti， and Zr. The carbides have an irregular shape， with small granular M23C6 primarily at the grain boundaries， along with a small amount of irregular MC-type primary carbide rich in Mo， Nb，and Ti. Based on the results of dendrite elimination， carbides re-dissolution， and changes in the residual segregation coefficients of three elements （Mo， Nb， Ti） after different homogenization treatments， it was determined that the homogenization process for a 12-ton C650 nickel-based alloy ingot should be 1 200 ℃-1 220 ℃ with a holding time of over 96 hours. Compared to the cast state， the samples after homogenization treatment show a significant improvement in high-temperature plasticity， which lays a favorable foundation for the smooth casting of the ingot.